Center-surround vs. distance-independent lateral connectivity in the olfactory bulb - Kim, David H.; Chang, Andrew Y.; McTavish, Thomas S.; Patel, Hetal K.; Willhite, David C. (Frontiers in Neural Circuits, 2012)
Lateral neuronal interactions are known to play important roles in sensory information processing. A center-on surround-off local circuit arrangement has been shown to play a role in mediating contrast enhancement in the visual, auditory and somatosensory systems. The lateral connectivity and the influence of those connections have been less clear for the olfactory system. A critical question is whether the synaptic connections between the primary projection neurons, mitral and tufted (M/T) cells, and their main inhibitory interneurons, the granule cells (GCs), can support a center-surround motif. Here, we study this question by injecting a “center” in the glomerular layer of the olfactory bulb with a marker of synaptic connectivity, the pseudorabies virus, then examine the distribution of labeling in the “surround” of granule cells. We use a novel method to score the degree to which the data fits a center-surround model vs. distance-independent connectivity. Data from 22 injections show that M/T cells generally form lateral connections with GCs in patterns that lie between the two extremes.